A Study of the AR Solutions Used in the Dangerous Goods Acceptance Process in Airport Cargo Warehouses - Anna Jodejko-Pietruczuk; Agnieszka A. Tubis; Franciszek J. Restel (Applied Sciences)
Background: The paper aims at answering cognitive questions which let one draw conclusions on AR usability in terms of supporting the dangerous goods acceptance (DGA) process before air transportation, including (1) which operations of the DGA process in airports reveal the highest potential in terms of being supported by AR solutions? (2) Which parameters of the DGA process can be improved by the use of AR solutions? (3) What benefits and drawbacks of solutions derived from the use of AR technology have been noticed in practical experiments? Research method: The study has been conducted by analysing the DGA process while considering the support of AR technology, the development of AR applications for AR goggles and a mobile phone, and their practical testing. Results: There has been a model of the DGA process has been developed in the paper as well as decision algorithms, helping operators controlling DGs before a flight, have been identified. Following these foundations, the design of functions supporting the DG acceptance process has been indicated and their expected influence on DGA results has been evaluated. Conclusions: The potential for AR support in DGA has been very positively assessed by experts; however, there have also been observed differences between functions that indicate the most promising and less promising aspects. Operators especially appreciate AR goggles when their goal is to show a virtual picture of data and related law regulations regarding controlled DGs, while interactions with AR goggles are assessed less positively. The results also prove that, at the present stage of technology development, AR tools can assist an operator and neither of the operations can be carried out automatically.